Treasury System and Organization of its Activities in Uzbekistan - Turgunmirzayevna, Komilova Shabnam; Ismatullaevich, Soliev Ibodulloxon (European Journal of Life Safety and Stability (2660-9630), 2021)
This article analyzes the introduction of the treasury system in our country and the achievements made as a result. Based on the results of the analysis, the prospects for further development of the system are given.